2004
DOI: 10.1111/j.1365-2141.2004.05257.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant deficit and enhanced susceptibility to oxidative damage in individuals with different forms of α‐thalassaemia

Abstract: Summary α‐Thalassaemia is a common red cell disorder in Taiwan, affecting 6–8% of Taiwanese. Previous studies have shown that reactive oxygen species are generated in increased amounts in thalassaemic red cells. This implies the possible alteration of redox status in thalassaemic patients, which may adversely affect their health. In the present study, the redox status of patients with α‐thalassaemia trait and haemoglobin H (Hb H) disease was investigated. Lipid peroxidation, as measured by the level of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 56 publications
0
22
1
Order By: Relevance
“…MDA levels were also elevated in β-TM patients (median [IQR], 30 nmol/ ml) with a range of 10-112 nmol/ml compared with the control group (median [IQR], 10 [7][8][9][10][11][12][13][14][15] nmol/ml; range 5-18 nmol/ml); p < 0.001 (Table 1 and Figure 1).…”
Section: Levels Of Ima and Mda In Patients With β-Tm And Healthy Contmentioning
confidence: 93%
See 1 more Smart Citation
“…MDA levels were also elevated in β-TM patients (median [IQR], 30 nmol/ ml) with a range of 10-112 nmol/ml compared with the control group (median [IQR], 10 [7][8][9][10][11][12][13][14][15] nmol/ml; range 5-18 nmol/ml); p < 0.001 (Table 1 and Figure 1).…”
Section: Levels Of Ima and Mda In Patients With β-Tm And Healthy Contmentioning
confidence: 93%
“…Liver lipid peroxidation also increases leakage of ferritin into the circulation. Levels of MDA have been reported to be correlated with iron concentrations in the liver as well as serum ferritin of thalassemia patients [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of mechanisms for an epistatic interaction seem plausible, a few of which are summarized here. Individuals with a 1 thalassemia are under increased oxidative stress, 41 a fact that likely relates to an intraerythrocytic excess of unmatched b chains and reactive free thiols.…”
Section: Discussionmentioning
confidence: 99%
“…16 In anemias, due to Thalassemia and G6PD enzyme deficiency, it has been shown that oxidative stress increases and antioxidant capacity is reduced. 17 In contrast, Acharya et al reported an increase in the levels of antioxidant enzymes in patients with iron deficiency anemia, and they suggested that this was due to overcompensation against the induced oxidative stress. 18 Al-Maskari et al reported that hyperhomocysteinemia with folate and vitamin B12 deficiency causes oxidative stress and there is also a parallel decline in the total antioxidant capacity.…”
Section: Discussionmentioning
confidence: 97%